Diabetes Mellitus Contributes to Idiopathic Pulmonary Fibrosis: A Review From Clinical Appearance to Possible Pathogenesis - Wang, Dongguang; Ma, Yao; Tong, Xiang; Zhang, Yonggang; Fan, Hong (Frontiers in Public Health, 2020)
Diabetes mellitus is a systematic metabolic disease characterized by persistent hyperglycemia, which complications often involve multiple organs and systems including vessels, kidneys, retinas and nervous system. Idiopathic pulmonary fibrosis is a chronic, progressive, fibrotic disease with usual interstitial pneumonia patterns. With in-depth research, diabetic-related lung injury has been confirmed, and the lung is also considered as one of the targeted organs of diabetes, which mainly manifests as the pulmonary fibrosis. Based on that, this review discusses the association between diabetes mellitus and idiopathic pulmonary fibrosis from clinical findings to possible underlying mechanisms.